Epidemiology of Diarrheagenic Escherichia coli: A Mini Review - Mohammed , Lalan Rebaz; Luo, Zuliang; Hama Soor, Taib Ahmed (Kurdistan Journal of Applied Research, 2024)
Diarrheal diseases are a significant public health challenge, leading to high numbers of morbidity and mortality globally. Diarrheagenic Escherichia coli (DEC) strains exhibit a complex spectrum, ranging from benign gut inhabitants to severe pathogens causing intestinal and extraintestinal diseases. This review focuses on elucidating DEC epidemiology, emphasizing research conducted worldwide. A comprehensive review searched for relevant studies on DEC's impact, using keywords like "diarrheagenic Escherichia coli," "DEC pathotypes," and "epidemiology" in databases like PubMed. Inclusion criteria covered 67 studies on virulence, pathogenesis, detection, and geographic diversity. Studies globally indicate variable prevalence rates for DEC. Enteropathogenic E. coli is prominent in Bangladesh (17.2% prevalence), relying on intimin, Bundle-forming pilus, and the locus of enterocyte effacement (LEE) pathogenicity island. Enterohemorrhagic E. coli, prevalent in the US and Europe (up to 1.5% outbreak rates in the US), utilizes Shiga toxin and the LEE pathogenicity island. Enteroaggregative E. coli, notably in Africa (Kenya, 13.5% prevalence), employs multilocus enzyme electrophoresis analysis, Escherichia coli heat-stable enterotoxin 1 (EAST-1), adherence mechanisms, and biofilm formation. Enterotoxigenic E. coli is highly prevalent in South Asia and Sub-Saharan Africa (Bangladesh, 6% prevalence), producing colonization factors and enterotoxins. Enteroinvasive E. coli is common in Asian developing countries like Bangladesh, relying on invasion genes and a large plasmid. Conversely, Europe exhibits notably low prevalence rates, with Enterohemorrhagic E. coli prevalence falling below 1%, especially in the UK. This review underscores the global prevalence of DEC, emphasizing the need for a global approach to disease management. Understanding the distinct virulence factors and pathogenesis of various DEC pathotypes is crucial for developing targeted interventions